Municipal Mayhem: Institutional, Political and Capacity Drivers of Poor Service Delivery in South African Local Governments - Isabirye, AK; Mkhabela, LZ (Journal of Ecohumanism, 2026)
This article examines why many South African municipalities fail to deliver basic services reliably, despite a robust constitutional mandate and recurrent reform efforts. The study aims to synthesize institutional, political and capacity explanations for municipal underperformance, trace the mechanisms linking these drivers to fiscal and operational collapse, and identify policy‑relevant remedies to avert systemic “municipal mayhem.” Adopting a qualitative literature‑review approach, the analysis draws on peer‑reviewed studies, policy reports and audit and survey data sourced from Google Scholar, JSTOR and EBSCOhost as well as AGSA, Statistics South Africa, COGTA, DBSA and civic surveys. The review finds that service‑delivery failure is produced by the interaction of weak financial management and revenue shortfalls, politicised appointments and interference, entrenched corruption, chronic skills and technical capacity gaps, inadequate infrastructure maintenance and legacy inequities from apartheid, all compounded by weak consequences for malpractice and uneven intergovernmental support. These dynamics generate fiscal unsustainability, poor audit outcomes, recurring protests and erosion of public trust. Recommended responses include reforming the municipal funding model to ensure predictable, equitable and conditional finance for core functions; strengthening fiscal oversight, procurement and consequence‑management regimes; prioritising targeted capacity development and professionalised administration; insulating technical functions from undue political interference; and aligning intergovernmental support to local context. We propose an integrated theoretical framework to guide empirical inquiry and pragmatic reform pathways for restoring municipal functionality.